182k views
9 votes
g(n)=−50−15ng, left parenthesis, n, right parenthesis, equals, minus, 50, minus, 15, n Complete the recursive formula of g(n)g(n)g, left parenthesis, n, right parenthesis. g(1)=g(1)=g, left parenthesis, 1, right parenthesis, equals

User Crazypeter
by
5.3k points

2 Answers

4 votes

Answer:

g(n) = g(n-1) -15

g(1) = -65

Explanation:

answer on khan

User Sol
by
5.1k points
13 votes

Answer:

g(n) = g(n-1) -15

g(1) = -65

Explanation:

We can find the recursive formula from the explicit formula for this arithmetic sequence by substituting 1 and (n+1) for n in the explicit formula.

__

g(n+1) = -50 -15(n+1) = (-50 -15n) -15 . . . . . find g(n+1)

g(n+1) = g(n) -15

and ...

g(1) = -50 -15(1) = -65

Then the recursive formula can ge written as ...

g(n) = g(n-1) -15

g(1) = -65

_____

Additional comment

We found g(n+1) = g(n) -15. Substituting n-1 for n in this formula puts it in the form we need for answering the question:

g((n-1)+1) = g(n-1) -15

g(n) = g(n -1) -15

Either of these forms tells you how to get the next term from the previous one.

User Sitram
by
5.6k points
Welcome to QAmmunity.org, where you can ask questions and receive answers from other members of our community.